Novel staging system using carbohydrate antigen (CA) 19-9 in extra-hepatic cholangiocarcinoma and its implications on overall survival. Issue 5 (May 2020) - Tella, Sri Harsha; Kommalapati, Anuhya; Yadav, Siddhartha; Bergquist, John R.; Goyal, Gaurav; Durgin, Lori; Borad, Mitesh; Cleary, Sean P.; Truty, Mark J.; Mahipal, Amit
Abstract: Background: CA19-9 elevation has shown to be associated with poor prognosis in extrahepatic cholangiocarcinoma (ECCA). However, the role of CA19-9 in staging of ECCA has not been evaluated. We hypothesized that CA19-9 elevation is a marker of aggressive biology in ECCA and that inclusion of CA19-9 in the staging system may improve overall survival (OS) discrimination. Methods: Patients with ECCA whose CA19-9 levels, irrespective of surgical status, were reported to the National Cancer Database (2004–2015) were included. The patients were classified based on their CA19-9 levels and a new staging system was proposed. Net reclassification improvement (NRI) model was used to assess the predictive improvement in the proposed survival model as compared to AJCC-TNM staging. Results: Of the 2100 patients included in the study, 626 (32%) and 1474 (68%) had normal and elevated CA19-9 levels (>38 U/ml), respectively. Median OS was lower among patients with elevated CA19-9 level compared to those with CA19-9 level ≤38 U/ml (8.5 vs 16 months, p < 0.01). On multivariate analysis, CA19-9 elevation independently predicted poor prognosis [HR:1.72 (1.46–2.02); p < 0.01] with similar impact as node-positivity, positive resection margins and non-receipt of chemotherapy. We developed a new staging system by incorporating CA19-9 into the 7th edition AJCC TNM staging system. NRI of 46% (95%CI: 39–57%) indicates that the new staging system is substantially effective at re-classifying events at 12 months as compared to AJCC 7th edition. Conclusion: Elevated CA19-9 was found to be an independent risk factor for mortality in ECCA and its inclusion in the proposed staging system improved OS discrimination.